Company Pension Plans, Stock Market Returns, and Labor Demand - Detragiache, Enrica (Washington, D.C. : International Monetary Fund, 2003)
With asset values falling sharply in recent years, many companies around the world are under pressure to restore the solvency of their defined-benefit pension plans. Will this lead to higher contributions? Will higher contributions increase labor costs and reduce employment? Does this mechanism exacerbate economic downturns? What are the economic effects of pension fund regulation? This paper develops a theoretical model to address these questions. Although its scope is more general, the model captures the main institutional features of the pension system in the Netherlands, a country where the economic effects of the pension shock are widely debated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet